1973
DOI: 10.1128/jb.113.1.58-70.1973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lethal Zygosis Associated with Conjugation in Escherichia coli K-12

Abstract: When F − cells are mixed with an excess of Hfr cells there is a lethal event which results in a decrease in the number of F − survivors. We have described and discussed the parameters affecting this phenomenon of lethal zygosis, and these include the cultural conditions of both donor and recipient cells prior to mixing and the use of aeration throughout the period of the experiment. The absence of lethal zygosis with filtrates and supernatant fluids from donors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Media. Nutrient broth, nutrient agar, and minimal agar (supplemented with glucose and growth factors as required for recombinant selection) were as previously described (34,35). Eosin-methylene blue agar (Difco-0511) was supplemented with galactose (0.5%, wt/vol) or lactose (1%, wt/vol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Media. Nutrient broth, nutrient agar, and minimal agar (supplemented with glucose and growth factors as required for recombinant selection) were as previously described (34,35). Eosin-methylene blue agar (Difco-0511) was supplemented with galactose (0.5%, wt/vol) or lactose (1%, wt/vol).…”
Section: Methodsmentioning
confidence: 99%
“…The derivatives of strain JC6256 carrying Col V2, ColVBTrp, R100-1, R136i-, R1-19, R386, and R538-ldrd (12, 49) were kindly provided by N. Willetts. Preparation of bacterial cultures. Bacterial cultures (usually in nutrient broth) were prepared as previously described (34,36). All cultures were incubated at 37 C.…”
Section: Methodsmentioning
confidence: 99%
“…Till now, experimental evidence demonstrating the selective advantages of exclusion has come from the characterization of lethal zygosis in the F plasmid (Skurray and Reeves, 1973;1974;Skurray et al, 1976;Ou, 1980). Recipients lacking the F plasmid (F-) are killed when mixed with an excess of Hfr or F+ exclusion-null donors.…”
Section: Selective Advantage Of Exclusionmentioning
confidence: 99%
“…In both instances, the donor-to-recipient ratio was 10:1 and conjugation was at 30 C for 60 min. Preliminary tests indicated that under these condi-tions lethal zygosis did not occur (32). From each mating experiment several hundred transconjugant colonies were scored.…”
Section: Ma3050 Of Devries Kl110/f103 Of Lowmentioning
confidence: 99%